El clima organizacional y el desempeño laboral de los trabajadores de Compartamos Financiera S.A. agencia Trujillo Centro - año 2016 - Vásquez Andrade, Sandra Fiorella (2017)
The purpose of this research work is to determinate the relationship between organizational climate and job performance of the employees at “Compartamos Financiera-Agency Trujillo Centre”, because of that two surveys were carried out, the first one was conducted to agency´s staff with regard to organizational climate, and the second one was conducted to the agency´s managers for the purpose of evaluating their employees. The survey sample was composed of total population, consisting of 60 employees. According to the results, it was concluded that there is a high relation between organizational climate and job performance of the employees of “Compartamos Financiera - Agency Trujillo Centro”. It was demonstrated that the agency has a good and friendly work environment and the employees’ job performance was good, highlighting the cooperation dimension. In sum up, it is recommended to develop an annual training program for agency´s employees and leaders, standardization of promotion process and implementing a employee recognition program, allowing the company to improve its short and long term management.